2005
DOI: 10.1007/s00228-004-0873-6
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of intravenous paracetamol in children and adolescents under major surgery

Abstract: Surgery, with all its potential influencing factors, together with chemotherapy given about 4 weeks previously do not seem to have a major impact on the pharmacokinetic behavior and the between-subject variability of paracetamol after intravenous administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 18 publications
4
24
0
Order By: Relevance
“…The range of median t1/2s we obtained (1.6 -2.2 h) for the paediatric age groups agrees with the range (1.0 -2.8) previously reported for both children and adults (Bannwarth et al, 1992;Autret et al, 1993;Prescott, 1996;Wurthwein et al, 2005). Being a derived PK parameter, t1/2 is related to the two fundamental PK parameters, Cl and Vd, (directly to clearance, and inversely to distribution volume), which explains why it is not also influenced by age in our study.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The range of median t1/2s we obtained (1.6 -2.2 h) for the paediatric age groups agrees with the range (1.0 -2.8) previously reported for both children and adults (Bannwarth et al, 1992;Autret et al, 1993;Prescott, 1996;Wurthwein et al, 2005). Being a derived PK parameter, t1/2 is related to the two fundamental PK parameters, Cl and Vd, (directly to clearance, and inversely to distribution volume), which explains why it is not also influenced by age in our study.…”
Section: Discussionsupporting
confidence: 92%
“…The PK values, CLt, Vd and t1/2, obtained were not significantly affected by age, weight, height, BMI or BSA, lending further support to the suggestion that the overall mechanisms involved in paracetamol elimination have reached adult capacity by the age of 2 years (Miller et al, 1976). Although the halflife for paracetamol obtained is similar to that reported by Wurthwein et al, (2005), the median values for the CLt/70 kg (21.7 -28.7 lh -1 ) are far higher compared to the 13.2 lh -1 reported by Wurthwein et al,. The reasons for this difference are not clear but could however be attributed to the size of study subjects recruited in the study by Wurthwein et al, which included only 7 subjects.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Only a limited amount of pharmacokinetic and pharmacodynamic studies have been performed with this formulation [4][5][6]. A study in a small group of healthy male volunteers showed a mean peak serum concentration (C max ), observed at the end of a 15-min i.v.…”
Section: Introductionmentioning
confidence: 99%